Mildly Reduced Brain Swelling and Improved Neurological Outcome in Aquaporin-4 Knockout Mice following Controlled Cortical Impact Brain Injury - Yao, Xiaoming (J Neurotrauma, 2015)
Brain edema following traumatic brain injury (TBI) is associated with considerable morbidity and mortality. Prior indirect evidence has suggested the involvement of astrocyte water channel aquaporin-4 (AQP4) in the pathogenesis of TBI. Here, focal TBI was produced in wild type (AQP4(+/+)) and knockout (AQP4(−/−)) mice by controlled cortical impact injury (CCI) following craniotomy with dura intact (parameters: velocity 4.5 m/sec, depth 1.7 mm, dwell time 150 msec). AQP4-deficient mice showed a small but significant reduction in injury volume in the first week after CCI, with a small improvement in neurological outcome. Mechanistic studies showed reduced intracranial pressure at 6 h after CCI in AQP4(−/−) mice, compared with AQP4(+/+) control mice (11 vs. 19 mm Hg), with reduced local brain water accumulation as assessed gravimetrically. Transmission electron microscopy showed reduced astrocyte foot-process area in AQP4(−/−) mice at 24 h after CCI, with greater capillary lumen area. Blood–brain barrier disruption assessed by Evans blue dye extravasation was similar in AQP4(+/+) and AQP4(−/−) mice. We conclude that the mildly improved outcome in AQP4(−/−) mice following CCI results from reduced cytotoxic brain water accumulation, though concurrent cytotoxic and vasogenic mechanisms in TBI make the differences small compared to those seen in disorders where cytotoxic edema predominates.